Psychometric testing of the indonesian version of beck depression inventory-ii among Indonesian floods survivors - Ariani, Tutu April; Anna, Anastasia; Rahayu, Henik Tri; Aini, Nur; Windarwati, Heni Dwi; Hernawaty, Taty; Mudiyanselage, Sriyani Padmalatha Konara; Lin, Mei-Feng (Jurnal Ners, 2023)
Introduction: Indonesia is a multi-linguistic country using the official language of Bahasa Indonesia. It is important to use formal language to collect research data without misinterpretation of study outcome and intervention effect with high accuracy. Therefore, this study aimed to analyze whether the Beck Depression Inventory-II (BDI-II) instrument translated into the Indonesian version was reliable and valid for measuring depression in floods-affected communities. Methods: The forward-backward translation was used to translate the BDI-II from English to Indonesian version. We tested the reliability and validity including content and construct validity through exploratory factor analysis (EFA) with varimax rotation and confirmatory factor analysis (CFA). We recruited 107 annual flood survivors in West Java, Indonesia as participants to test the psychometric testing. Results: The structures shown by the EFA are two factors, with Factor 1 representing negative cognitive-attitude domains and somatic symptom items consisting of Factor 2. The CFA concludes that the general factor model best fits the data on the basis Goodness-of-Fit Index (GFI)= 0.8; Root Mean Square Error of Approximation (RMSEA)= 0.09; Standard Root-Mean-Square Residual (SRMSR)); Comparative Fit Index (CFI)= 0.81; Tucker–Lewis Index (TLI)= 0.79; and p-value Ï‡2 = < 0.01, Ï‡2/df: 1.82). Conclusions: The results showed that the BDI-II Indonesian version has good reliability and validity and can be used to measure depression status among people who suffer floods in community setting. Future studies need to be validated within multiple socio-cultural groups.